Pembelajaran Berdiferensiasi pada Mata Pelajaran PAI: Tinjauan Literatur Berbasis Dimensi School Well‑Being - Cahyono, Acep; Wahyuni, Ana Dwi; Umam, Mustolikh Khabibul (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2025)
This literature review article discusses differentiated learning in Islamic Religious Education (PAI) based on four dimensions of school well-being: having, loving, being, and health. The study aims to summarize empirical and conceptual findings regarding differentiation strategies that support students' holistic well-being. The method includes a systematic search of literature on Google Scholar (2016–2025, Sinta 1–6) using the keywords "differentiated learning", "Islamic Religious Education", and "school well-being", then descriptive-analytic analysis to map themes per dimension. The results show that the differentiation strategy of content, process, product and environment can increase the availability of materials (having), strengthen social and emotional relationships (loving), facilitate self-actualization and reflection (being), and maintain physical and mental health through kinesthetic and mindfulness activities (health). The integration of the four dimensions produces a comprehensive framework that not only improves academic outcomes but also maintains students' emotional, social, and spiritual well-being. These recommendations can be practical guidelines for PAI teachers and curriculum developers.